EXPLORING THE RELATIONSHIP BETWEEN PHYSICAL ACTIVITY AND LIFE SATISFACTION AMONG INTERNATIONAL STUDENTS AT INDONESIAN UNIVERSITIES LOCATED IN JAVA - Salman, Muhammad; Perdana, Satya; Nugroho, Sigit; Nasrulloh, Ahmad (MEDIKORA, 2025)
Internationalization has grown from an insignificant challenge to a crucial priority in recent decades, becoming a vital part of global higher education systems. The key objevtive of this study was to investigate the relationship between physical activity and life satisfaction among international students attending Indonesian institutions in Java. Importance to promoting their overall well being and adaptation in a foreign academic evironmentThis study included 220 foreign students (121 (55%) male, aged 18 to 52, mean age 26.7 and SD = 5.9 years old) from various countries who were studying at several institutions in Java, Indonesia. Physical activity data were collected using IPAQ(International Physical Activity Questionnaire), and life satisfaction was measured using the Satisfaction with Life Scale (SWLS). The non probability convenience sampling method used to collect the data and pearson statistical used to analysis the correlation between life satisfaction and physical activity. The findings showed that life satisfaction and physical activity were strongly positively correlated, with a Pearson correlation coefficient (r) of 0.806, the coefficient of determination (R2) was 0.63, indicating that variations in physical activity levels account for 63% of the variance in life satisfaction. A p-value of 0.002, well below the conventional threshold of 0.05, validated the statistical significance of this association. Regular physical exercise was associated with better levels of life satisfaction among international students. These results emphasise how important it is to include physical exercise in daily routines in order to increase foreign students' life satisfaction. To further understand the basic processes and show how physical activity and life satisfaction are related in this student population, more study is required.